Islamic Values and Islamic Branding: A New Perspective on College Choice Decisions in Indonesia - Yayuk Sri Rahayu; Fitriyah Fitriyah; Guntur Kusuma Wardana; Wan Nur Fazni Wan Mohamad Nazarie (al-Uqud : Journal of Islamic Economics, 2025)
This study aims to analyze the influence of Islamic values and Islamic branding on decisions and intention in choosing higher education institutions in Indonesia, examine the impact of intention, Islamic values, and Islamic branding on decisions to select higher education institutions in Indonesia, and identify the key determinants influencing these decisions. An explanatory mixed-method approach was employed, conducted in two stages: starting with quantitative research followed by qualitative research. The population comprised university students in Indonesia, with the sample consisting of students in at least their third semester. The study involved 207 respondents, with quantitative data analyzed using PLS and qualitative data collected through questionnaires and focus group discussions (FGDs). The findings reveal that Islamic values and Islamic branding significantly influence the decision to choose a higher education institution in Indonesia. While Islamic values impact intention, Islamic branding does not affect intention in higher education institutions in Indonesia. Moreover, intention does not influence decisions to select higher education institutions. Additionally, Islamic values and Islamic branding do not indirectly affect decisions through intention. Five main factors were identified as key determinants in selecting higher education institutions: accreditation and institutional reputation, availability of study programs and supporting facilities, Islamic culture and environment, affordability and cost, and location and accessibility